The Creativity of Mentally Retarded Students in Solving Plane Problems with Image Media - Ambar Ningrum Yelly Astuti; Betty Kusumaningrum; Sri Adi Widodo; Novi Asmarani Kusuma Dewi; Muhammad Irfan (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
Mental retardation is a condition of someone who has intellectual skills below average. For this reason, the learning process for mentally disabled students requires a different strategy when compared to learning for regular students. Mathematics has the characteristics of an abstract concept. Learning requires media so that the message conveyed by the teacher to students can be adequately achieved. For this reason, learning mathematics requires media such as pictures. In this regard, the purpose of this study was to determine the increase in the creativity of mentally disabled students in solving mathematical problems using media images. This study used one subject with mental retardation characteristics selected by purposive sampling. This single-subject research uses an ABA design. The instrument used in this study was a mathematical creativity test given to subjects in each session. Data analysis techniques use visual techniques, including analysis within and between conditions. The results showed that the subjects were in stable condition at the first baseline, with an average of 66.63. The issues were stable at the intervention, with an average of 79.18. in the retrieval or the second baseline phase, the subjects were in an unstable situation with an average of 62.72. Apart from that, in between conditions, it was found that between the first conditions had increased. Between the second condition, it decreased because media images were not used in learning mathematics. These results indicate that using media images can improve the creative mathematical abilities of mentally disabled students.